Statistical Modeling and Optimization of Mechanical Properties for Solidified Polylactic Acid Parts Fabricated By Fused Filament Modeling Process - Khatwani, Jagdish (My University, 2016)
3D Printing is a layered manufacturing process that builds prototypes by depositing material in layered form using heaters. Prototypes made by 3D Printing are widely used in product development as they can be used for product testing. Prototypes should have a very good mechanical properties for functional performance as well as aesthetics. The mechanical properties in 3D printing depends upon different process parameters, namely Layer Thickness, Nozzle Diameter, Part Bed Temperature, Speed of Deposition, Raster Angle of Deposition, Raster Width and Length of the parts. In this present work, an attempt has been made to improve the mechanical properties namely, tensile strength, flexural strength and impact strength of prototypes of Solidified PolyLactic acid parts fabricated using Fused Filament Modelling process of 3D Printing. Experiments have been performed according to Central Composite Rotatable Design (CCRD) considering three parameters namely layer thickness, nozzle diameter and part bed temperature of parts at three levels. Empirical statistical models have been developed for predicting the tensile strength, flexural strength and impact strength of the parts. Analysis of variance (ANOVA) has been used to test the significance of process variables on these mechanical properties. In case of tensile strength, layer thickness and part bed temperature are found significant parameters. Flexural strength is mainly affected by layer thickness, followed by part bed temperature and nozzle diameter. In case of impact strength, layer thickness and nozzle diameter are found to be significant. Confirmation of statistical model have been done by estimating the error and performing experiments at different parameters other than experiments in DOE and the results were found to be satisfactory. Optimization for the maximization of tensile strength, flexural strength and impact strength have been done using trust region based MATLAB technique. SEM has been used to understand the mechanics of fracture in testing for tensile strength, flexural strength and impact strength.
Keywords: 3D Printing; PolyLactic Acid; Tensile Strength; Flexural strength; Impact strength; Part Bed Temperature; Layer Thickness; Nozzle Diameter